2006
DOI: 10.1039/b611311g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Claisen rearrangement of bridged bicyclic enol ethers of relevance to the course of ketene s-cis-diene cycloaddition

Abstract: The synthesis is described of a range of 3-alkylidene-2-oxabicyclo[2.2.1]hept-5-ene and 3-alkylidene-2-oxabicyclo[2.2.2]oct-5-ene derivatives; Claisen rearrangement of these substrates either thermally or in the presence of an added Lewis acid results in the formation of bicyclic cyclobutanones with generally good conversions. These reactions may be performed in hydroxylic solvents, supporting a largely non-dissociative pathway for the rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Atualmente, os principais métodos de preparação de THMCs ainda envolvem as reações do ânion tri-halometila com espécies carboniladas, especialmente aldeídos, a partir de: CHX 3 , em meio básico; [13][14][15][16][17][18][19][20][21][22][23][24] ácido tri-haloacético e tri-haloacetato, 25-27 conforme o Esquema 3.…”
Section: Tri-halometil Carbinois -Thmcsunclassified
“…Atualmente, os principais métodos de preparação de THMCs ainda envolvem as reações do ânion tri-halometila com espécies carboniladas, especialmente aldeídos, a partir de: CHX 3 , em meio básico; [13][14][15][16][17][18][19][20][21][22][23][24] ácido tri-haloacético e tri-haloacetato, 25-27 conforme o Esquema 3.…”
Section: Tri-halometil Carbinois -Thmcsunclassified
“…These results are consistent with the related Claisen rearrangement believed to follow 4 + 2-cycloaddition of ketene derivatives to cyclopentadiene, the sequence leading to the observed products of this cycloaddition, the bicyclo[3.2.0]hept-5-en-2-one derivatives. 10 The decarboxylative Claisen rearrangement of allylic tosylacetate (5) and methyl tosylmalonate derivatives has been extensively studied. In the tosylacetate series, it has been found that acetate ions, base and a silylating agent, preferably N ,Obis(trimethylsilyl)acetamide (BSA), are all necessary, but in only catalytic quantities provided that BSA is used.…”
Section: One Heteroatommentioning
confidence: 99%
“…For related literature, see: Yamabe et al (1996); Machiguchi et al (1999); Khanjin et al (1999); Ussing et al (2006); Robertson & Fowler (2006). Mo K radiation = 0.59 mm À1 T = 150 K 0.44 Â 0.32 Â 0.18 mm…”
Section: Related Literaturementioning
confidence: 99%
“…The situation is, however, more complex and a combined theoretical and experimental study of the reaction of cyclopentadiene with either dichloro-or diphenylketene revealed that both [4 + 2] and [2 + 2] adducts may be produced directly through parallel reaction pathways traversing a bifurcating energy surface (Ussing et al 2006). Our studies sought to address certain mechanistic aspects of the Claisen rearrangement of bicyclic enol ethers structurally analogous to those produced in diene/ketene [4 + 2] cycloadditions (Robertson & Fowler, 2006); within this study, although crystals were obtained as a racemate, the title compound was prepared in an enantioenriched form in order to determine if access to non-racemic cyclobutanones could be achieved.…”
Section: Data Collectionmentioning
confidence: 99%